Evaluating the biological conversion of paddy husk to house fly, Musca domestica L (Diptera: Muscidae) pupa powder: a study of house fly as animal feed - Ong, Song-Quan; Hamdan Ahmad, (Pusat Sistematik Serangga, Fakulti Sains dan Teknologi, Universiti Kebangsaan Malaysia, 2015)
The sector of livestock and aquaculture are growing rapidly in order to meet the incremental demand of essential protein for the world’s population. However, the supply of plant-based animal feed was limited by resources such as land and water. The opportunity for insect as the substitute to animal feed is tremendous; nonetheless, little attention was taken in Malaysia. In this study, low value bio-waste, paddy husks, which were in pellet form were prior ground and dried, then fed to larva of common house fly, Musca domestica L (Diptera: Muscidae).House fly pupae were collected, dried and ground into powder for analysis. Weight-conversion and nutrition value were studied by applying standard AOAC and FAO methods. The paddy husk to pupa weight conversion was 4.10%, in other words, 41g housefly pupae powder could obtained from 1kg of paddy husk. For the nutritional analysis, house fly pupae powder consists of 68.90% crude protein, which was significantly higher that the paddy husk (15.65% crude protein, <0.001). This study indicating a significant conversion of a low value material to highly protein contained animal feed and this transformation was crucial in providing an alternative solution for animal feed.